Changes in Cadmium Concentration in Muscles, Ovaries, and Eggs of Silver European Eel (Anguilla anguilla) during Maturation under Controlled Conditions - Joanna Nowosad; Dariusz Kucharczyk; Mariusz Szmyt; Joanna Łuczynska; Müller Tamás; László Horváth (Animals, 2021)
This study determined the contents of cadmium (Cd) in the muscles, ovaries, and eggs of silver female European eels. The analysis of cadmium content was performed on female European eels caught during commercial fishing in freshwater in Warmia and Mazury (Poland), and then subjected to artificial maturation and ovulation processing under controlled conditions. The content of cadmium (Cd) in the tissues was determined by flameless atomic spectrometry using an electrothermal atomizer. The analysis showed statistically significant differences between the cadmium content in the muscles, ovaries, and eggs (p < 0.05) of female European eels. The lowest cadmium content was found in the muscle tissue (0.0012 ± 0.0001 mg kg−1 wet weight) and the highest in eggs (after ovulation) (0.0038 ± 0.0007 mg kg−1 wet weight). Moreover, a relationship was found between the cadmium content in the muscle tissue and the ovaries (R = 0.673; p = 0.0117) in the same fish. The movement of cadmium from tissues to oocytes may indicate a significant problem concerning this heavy metal content in the reproduction of European eel.